North Bathurst Island Groundwater Assessment - Woltmann, Melissa (Department of Land Resource Management, 2017)
A hydrogeological investigation was undertaken in 2014 as part of a broad assessment of the natural resources in the North Bathurst Island area. This information is intended to provide a basis for the assessment of the suitability of the area for horticulture or other developments. The focus of the groundwater study was to characterise and elucidate the shallow unconfined aquifer hosted in the Van Diemen Sandstone, with some scope to investigate the deeper confined aquifer within the Moonkinu Sandstone. This report details the findings of the study. Executive summary -- Introduction -- Hydrogeology -- Geology -- Aquifer Occurrence and Extent -- Aquifer Parameters -- Groundwater Movement and Recharge -- Water Quality -- Bore Yield Potential -- Conclusions -- Recommendations -- References This report has two volumes - Volume 1 Main report and Volume 2 - Appendices